Temperature effects on singlet fission dynamics mediated by a conical intersection - Sun, Kewei (2021)
Finite-temperature dynamics of singlet fission in crystalline rubrene is investigated by utilizing the Dirac-Frenkel time-dependent variational method in combination with multiple Davydov D2 trial states. To probe temperature effects on the singlet fission process mediated by a conical intersection, the variational method is extended to include number state propagation with thermally averaged Boltzmann distribution as initialization. This allows us to simulate two-dimensional electronic spectroscopic signals of two-mode and three-mode models of crystalline rubrene in the temperature range from 0 K to 300 K. It is demonstrated that an elevated temperature facilitates excitonic population transfer and accelerates the singlet fission process. In addition, increasing temperature leads to dramatic changes in two-dimensional spectra, thanks to temperature-dependent electronic dephasing and to an increased number of system eigenstates amenable to spectroscopic probing.